The influence of smoking on the levels of matrix metalloproteinase-8 and periodontal parameters in smoker and nonsmoker patients with chronic periodontitis: A clinicobiochemical study - Namita Gupta; Narinder Dev Gupta; Lata Goyal; Shagufta Moin; Saif Khan; Akash Gupta; Sagar Garg (Journal of Oral Biology and Craniofacial Research)
Aims: Even though worldwide evidences tend to prove that smoking adversely influences periodontal health, there are few studies demonstrating the effect of levels of salivary matrix metalloproteinase-8 (MMP-8) in smokers. This study aimed to compare and quantify the levels of MMP-8 in smokers and also to evaluate the effect of smoking on periodontal indices in smokers and nonsmokers with chronic periodontitis. Methods: A total number of 60 subjects were selected for the study and were divided into three groups: group I, healthy nonsmoking subjects; group II, nonsmoking patients with chronic periodontitis; group III, smoking patients with chronic periodontitis. Each group consisted of 20 subjects. Saliva sample was collected for the estimation of MMP-8 by enzyme-linked immunosorbent assay (ELISA) method using Quantikine human total MMP-8 immunoassay kit. Results: The levels of the salivary MMP-8 of group III was highest followed by group II and group I, the least. The other periodontal indices, viz. plaque index (PI), probing pocket depth (PPD), clinical attachment level (CAL), were highest for group III, except for gingival index (GI). Conclusion: This study suggests that MMP-8 is involved in periodontal destruction associated with smoking. Additionally, smoking exerts disastrous effects on immune response and can affect the pathogenesis of disease; hence, smoking results in increased severity of periodontal destruction.